Food as Outreach: Bridging Social Boundaries with Sacred Feasts - Rigney, Cressida (Journal for the academic study of religion, 2016)
Food is a medium for extending charity and constituting community, in the face of social and cultural divisions, based on perceptions of purity. The work of charitable groups The Red Frogs, The Homeless Run, and Reverend Bill Crews' Loaves and Fishes in contemporary Australia creates links between cultural and spiritual food practices of religious and secular groups. Food charity transcends boundaries embracing the marginalised and needy groups of society, building temporary and permanent nourishing communities, while rejecting tensions of purity-based social division. This is the first academic treatment of all three charities, which have to date been featured only in the popular media. Food charity extends commensality to those who are frequently separated from the charity providers. This feeds physical and spiritual needs of both benefactors and beneficiaries. The benefactors accrue a sense of personal success in living out their faith and the needy experience purposefully given commensality and acceptance. Such charitable actions challenge the notions of purity that divide people, demonstrate the importance of practical faith, and utilise the power of food regularly to build temporary and permanent communities based on care and commensality. They work to protect, nourish, enrich, and elevate the lives of those who benefit from the food distributed, rejecting social division on the basis of socially constructed understandings of purity.